2010
DOI: 10.1136/bcr.11.2009.2441
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab (Avastin) associated with secondary hyphaema in a case of proliferative sickle cell retinopathy

Abstract: Intravitreal bevacizumab (Avastin) has been used off label for various conditions, including proliferative sickle cell retinopathy (PSR). Some authors have reported a more rapid resolution of the vitreous haemorrhage in Goldberg stage 4 PSR. Following injection of 1.25 mg of bevacizumab in each eye in a case of PSR (right eye with stage 3 sea fan neovascularisation and left eye with organising vitreous haemorrhage), we recently found a surprising association with significant secondary hyphaema on the fifth day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…Intravitreal bevacizumab can be used as a pre-surgical adjunctive agent to decrease the risk of intraoperative bleeding and facilitate dissection of sea fan neovascular structures [69][70][71]. Although preoperative bevacizumab may be efficient, secondary hyphaema, a few days post-injection, is a possible complication [72]. Cai et al recently described five eyes of five patients with PSR that were managed with intravitreal bevacizumab therapy over a 13-year period [73].…”
Section: Intravitreal Injection Of Anti-vascular Endothelial Growth Fmentioning
confidence: 99%
“…Intravitreal bevacizumab can be used as a pre-surgical adjunctive agent to decrease the risk of intraoperative bleeding and facilitate dissection of sea fan neovascular structures [69][70][71]. Although preoperative bevacizumab may be efficient, secondary hyphaema, a few days post-injection, is a possible complication [72]. Cai et al recently described five eyes of five patients with PSR that were managed with intravitreal bevacizumab therapy over a 13-year period [73].…”
Section: Intravitreal Injection Of Anti-vascular Endothelial Growth Fmentioning
confidence: 99%
“…Bevacizumab, albeit efficient in preoperative injection, 80 was associated with significant secondary effects such as secondary hyphema few days postinjection in the eye of a PSCR patient with VH. 81 Clinical trials aiming to compare efficacy and safety of ranibizumab versus aflibercept, in patients with SCR versus patients with diabetic retinopathy, would be an asset.…”
Section: Current and Advanced Therapeutic Options For Scrmentioning
confidence: 99%
“…His BCVA was improved from 20/40 to 20/20, the vitreous hemorrhage was resolved, and the neovascularization regressed, presenting no recurrence at the 6-month follow-up [ 20 ]. Contrary to Siqueira et al and Shaikh, Babalola reported no resolution of vitreous hemorrhage and development of hyphema after intravitreal injection of bevacizumab for sickle cell retinopathy in a 25-year-old male patient, while in the other eye regression of stage III sea fan neovascularization was remarked [ 21 ]. Our case is the first one, using intravitreal ranibizumab for the treatment of stage IV sickle cell retinopathy, showing promising results.…”
Section: Discussionmentioning
confidence: 98%